2017
DOI: 10.1177/2397847317707370
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to the safety assessment of food additives in early life

Abstract: During the development of international standards by the Codex Alimentarius Commission, infant foods and their constituent ingredients are subject to rigorous risk analysis and are strictly regulated by many authorities. Various jurisdictions have approved only a limited number of additives specifically with regard to infant foods to fulfill specific technical requirements of quality. As part of the approval process, a rigorous safety assessment is essential to confirm that the use of additives does not pose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 117 publications
(162 reference statements)
0
3
0
Order By: Relevance
“…In the head, gills, abdomen, tails, fins, and scales of the Hypophthalmichthys molitrix , the concentration of Pb was found maximum (15.60, 17.15, 20.20, 14.32, 20.10, and 22.50 mg/kg, respectively), while Cd showed the minimum concentration (0.032, 0.112, 0.112, 0.096, 0.064, and 0.016 mg/kg, respectively). The concentrations of lead, nickel, and iron, described by the WHO were above the permissible levels, while the concentrations of chromium, copper, zinc, and cadmium were below the permissible limits [ 25 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the head, gills, abdomen, tails, fins, and scales of the Hypophthalmichthys molitrix , the concentration of Pb was found maximum (15.60, 17.15, 20.20, 14.32, 20.10, and 22.50 mg/kg, respectively), while Cd showed the minimum concentration (0.032, 0.112, 0.112, 0.096, 0.064, and 0.016 mg/kg, respectively). The concentrations of lead, nickel, and iron, described by the WHO were above the permissible levels, while the concentrations of chromium, copper, zinc, and cadmium were below the permissible limits [ 25 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 4, along with health benefits that have been ascribed to them and pertinent toxicological data. The authors recognize that lack of knowledge about the metabolism of food additives old or new, difficulties in determining accurate levels of exposure, and susceptibility to toxicity have historically hindered safety assessments in the neonatal context (150). Likewise, the purported health benefits noted in Table 4 are largely derived from animal studies or human feeding trials conducted with children or adults, and extrapolation of results to the neonatal situation is challenging.…”
Section: Nutritional Toxicological and Regulatory Considerationsmentioning
confidence: 99%
“…According to Constable et al, 25 who recently extensively discussed an integrated approach to the safety assessment of food additives in early life, currently there is neither scientific consensus nor guidance from regulatory bodies on the most suitable animal species to address toxicological data gaps in the early life period. It is suggested that the early life stage of pigs is close to human early life stage.…”
Section: Introductionmentioning
confidence: 99%